PERSEPSI ORANG TUA SISWA TERHADAP KUALITAS PELAYANAN PEMBELAJARAN JARAK JAUH (PJJ) DI MTS ANNAJAH JAKARTA - Saputra, Robbi (Jurnal Analisis Pendidikan Sosial, 2025)
This study aims to find out the opinions of parents’ students regarding the learning provided by MTs Annajah teachers during the COVID19 pandemic through distance learning. Distance learning separates educators and students through online or e-learning. so this learning process involves parents whose benefits are felt by the parents of students. Because after all the parents of students must be served well regarding matters of school learning. The method used in this research is a qualitative approach. The population in this study were all parents’ and students of MTs Annajah, totaling 432 people. The sample in this study amounted to 65 people. Data collection was carried out by online survey using google form. The results showed that the average student's parents were satisfied with the services provided by MTs Annajah teachers with a percentage of above 50%.